EVALUATION OF MICROALGAE AS A NATURAL FOOD SOURCE (Scientific journal of the Fergana State University, 2024)
Increasing fish productivity by growing Daphnia genera, which are used as trick feed for fish, in artificial water reservoirs with high nutritional value microalgae (Chlorella, Ankistrodesmus, Scenedesmus, Botryococcus, Chlorococcum). Therefore, on the basis of them, the production of high-quality and low-cost protein and fat was researched.